Generasi Z Dalam Memanfaatkan Media Sosial - Widiani, Sri (STAIN Bengkalis, 2022)
: The development of technology has experienced rapid progress, one of which is the existence of social media. Technology began to develop in the era of generation z, where generation z is the one who gets the impact of technological developments. Social media never escapes daily use. Apart from being a liaison for social media communication, it also received a good response in education, which made it easier for teachers to make teaching materials more effective and made it easier for teenagers to access something. Besides the benefits of technological advances, there are also negativ impacts that have emerged. In this case, it will be explained some of the benefits and problems that arise in technological advances in the era of generation z . Based on qualitative data collected from literacy results in several journals that will strengthen this discussion